A case report on ovarian torsion after ovarian stimulation - Lakshmana, Veena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ovarian torsion is a rare but serious cause of acute abdominal and pelvic pain in women, accounting for 2.7% of gynecologic emergencies. The incidence of ovarian torsion has been reported to be increased due to ovarian hyper stimulation. The incidence increased to 6 % under stimulation for assisted reproductive technology (ART) and to 16 % with ovarian hyperstimulation syndrome (OHSS). Although the delay in diagnosis from symptom onset is common, rapid diagnosis of ovarian torsion is imperative to prevent morbidity. The gold standard to treat ovary torsion is surgery, and this is also the only way to confirm the torsion. Here is a case report of a 31-year-old lady with a history of infertility underwent two cycles of ovulation induction and intrauterine insemination (IUI), presented with acute pain abdomen as well as a history of a similar episode two months earlier. A preoperative diagnosis of an ovarian cyst with suspicion of torsion was made and laparoscopy was performed. Intraoperative diagnosis of left ovarian torsion due to dermoid cyst was done and ovary untwisted and fixed to the round ligament, cyst was removed, and ovarian tissue was conserved. Patient was followed up until pregnancy and delivery.